Surgical Management of Multiple Valve Endocarditis Associated with Dialysis Catheter - R. Zea-Vera; M. Sanchez; E. Castañeda; L. Soto-Arquiñigo (Case Reports in Infectious Diseases)
Endocarditis associated with dialysis catheter is a disease that must be suspected in every patient with hemodialysis who develops fever. Multiple valve disease is a severe complication of endocarditis that needs to be managed in a different way. There is very limited data for treatment and every case must be considered individually. We present a patient with this complication and describe the medical treatment and surgical management. We report the case of a 15-year-old patient with acute renal failure that develops trivalvular endocarditis after the hemodialysis catheter was placed, with multiple positive blood culture for Staphylococcus aureus. Transesophageal echocardiography was done and aortic and tricuspid valvular vegetations and mitral insufficiency were reported. Patient was successfully treated by surgery on the three valves, including aortic valve replacement. There is limited data about the appropriate treatment for multiple valvular endocarditis; it is important to consider this complication in the setting of hemodialysis patients that develop endocarditis and, despite the appropriate treatment, have a torpid evolution. In countries where endovenous drug abuse is uncommon, right sided endocarditis is commonly associated with vascular catheters. Aggressive surgical management should be the treatment of choice in these kinds of patients.